MARKETING STRATEGY FOR CONSTRUCTING AND PROMOTING LOW-RISE BUILDINGS - MAKATORA, Dmytro; KUBANOV, Ruslan; YASHCHENKO, Oleksii (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The study presents the theoretical and methodological foundations for developing a marketing strategy for constructing and promoting low-rise buildings. Building and promoting low-rise housing requires an integrated approach and effective marketing strategy. The authors have identified a number of useful steps in this direction. Studying the target audience is the first step in developing a marketing strategy for such buildings. There is a need for market research, identification of the needs and requirements of future buyers, as well as their social and financial characteristics. Defining a unique offer is the second important aspect. This may involve using advanced construction technologies, increasing energy efficiency, innovative design or creating a convenient layout. Uniqueness makes a project attractive to consumers and differentiates it from the competition. One of the key aspects of a marketing strategy is to advertise and promote. The selection of the right communication channels is a key factor in the reach of the target audience. Some of the tools that can be used to promote low-rise buildings include internet marketing, social media, visual advertising, participation in exhibitions and presentations. It’s also important to remember to keep interacting with potential clients while building. This can include regular visits to the construction site, advice on the process of buying a house, and support for the customer after the building has been put into use. In conclusion, the marketing strategy for low-rise housing should be unique, customer-centric and effective in the promotion of the product. A well-constructed strategy will not only help to attract buyers, but will also create a positive image of the company. This will increase sales and compete successfully in the marketplace. Success in this area can be achieved through a thorough analysis of the target audience, the use of modern marketing tools and cooperation with experts.
Keywords: marketing strategy; low-rise building; real estate market; construction object; segmentation; target audience; unique offer; communication channels